Profile Of Neonatal Admission At Chitwan Medical College - Shrestha, SP; Shah, AK; Prajapati, R; Sharma, YR (Journal of Chitwan Medical College, 2014)
In Nepal, three most common causes of newborn (NB) admission in the neonatal intensive care unit (NICU) are birth asphyxia, neonatal sepsis and prematurity and they are the leading causes of death too. A study previously done in Nepal shows asphyxia as a leading cause of hospital admission accounting 22% followed by prematurity 20% and neonatal sepsis 17% with mortality due to these three causes being 7%, 3% and 5% respectively. Reasons of NICU admission in Chitwan Medical College (CMC) are clinical sepsis in 50% of cases followed by birth asphyxia 17.6%, and prematurity in 6.7% cases. Respiratory distress syndromes (RDS), neonatal jaundice, congenital hydrocephalus, meningitis are other reasons of NICU admission. Most of the babies were delivered by normal vaginal delivery at health facility 53%, and 47% of NB was delivered through lower section Caesarean section (LSCS). Only 6% of NB was having birth weight of less than 1.5 kg and majority of them were above that. There were 65% NB who was born at term and remaining 35% were preterm. Majority of NB were admitted within 72 hours of birth with 79% of the total admission. Hypoglycemia was observed in 83 out of 202 newborns accounting 41% neonatal hypoglycemia at birth. Journal of Chitwan Medical College 2013; 3(4); 13-16 DOI: http://dx.doi.org/10.3126/jcmc.v3i4.9547